Investment in photovoltaic energy: An attempt to frame Brazil within the 2030 passage target of the Paris agreement - Saccardo, Ronaldo Ricardo [UNESP]; Domingues, Ana Mariele [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP]; Bezerra, Barbara Stolte [UNESP]; Siqueira, Regiane Maximo [UNESP]; Neto, João Batista Sarmento dos Santos (Elsevier, 2023)
Energy generated by fossil fuels is the main source of GHG emissions in the world. To mitigate global warming, Paris Agreement is an initiative that aims to limit global GHG emissions. Substitution of fossil fuels by renewable sources is considered a solution to reducing GHG emissions. Solar energy is particularly emphasized due to its high availability and low emissions. Although Brazil has excellent conditions for the generation of photovoltaic solar energy, its energy matrix is still composed of a large amount of fossil sources. There is a lack of studies on the change in GHG emissions by replacing these fossil sources with photovoltaic energy and the investment required for this change. This article aims to investigate GHG emissions of projected energy matrix of Brazil in 2030 and investment needs in photovoltaic energy for replacement of fossil sources, seeking an energy matrix within the goals Paris Agreement. Projections for substituting fossil fuels with photovoltaic energy in the year 2030 were made and GHG emissions in CO2eq were calculated using the IPCC method for Global Warming Potential - 100 years. The annual investment was estimated using data on capacity factor of photovoltaic generation for Brazil and value of installation costs provided by International Renewable Energy Agency. Results revealed that with the projected substitution of fossil fuels by photovoltaic in matrix energy 2030 emissions can be reduced by 36,9% (from 0.484GtCO2eq to 0,305GtCO2eq). The investment required for this replacement is estimated at U$S 376,5 billion. Despite the photovoltaic energy promising type of energy for Brazil, it is still unfeasible for the country to achieve goals in Paris Agreement (0,187 GtCO2e for 2030). In addition, a SWOT analysis provides an overview for decision-makers on strengths, weaknesses, opportunities and threats of photovoltaic energy in mitigation climate change context.
Keywords: Energy efficiency; GHG; Greenhouse gas; Paris agreement; Photovoltaic energy; Renewable energy